The Effect of Study Costs, Brand Image, and Quality of Services on Decision to Choose the Faculty of Medicine University Prima (UNPRI) Medan - Nigel Alvio Chrislando; Fenny Krisna Marpaung; Sarah Elisabeth Sitohang; Michael Yosua Toni Sitompul; Kirsni Hareyani (Journal of Research in Business, Economics, and Education, 2022)
The purpose of this study is to find out how influential price is on a purchase decision, to find out how influential brand image is to a purchase decision, to know how influential service quality is to a purchase decision and to know how influential price, brand image and service quality are simultaneously. a purchasing decision for students of the Faculty of Medicine UNPRI Medan. This research was conducted on students of the Faculty of Medicine UNPRI Medan. The population, namely all educational staff at the Faculty of Medicine UNPRI Medan, is 80 people. The sampling technique was calculated by the Slovin formula so that a sample of 80 people. The results of the study are the price tcount value of 3.100 > 1.990 and sig <0.05 (0.003 <0.05), the tcount value of brand image is 4.727 > 1.990 and sig <0.05 (0.000 <0.05), the tcount value of service quality of 2.396 > 1.990 and sig < 0.05 (0.019 < 0.05), and the Fcount value of price, brand image and service quality simultaneously is 21.930 > 2.487 and sig < 0.05. The adjusted RSquare is 0.643 / R2 x 100%, which is 64.30%, this shows that the research independent variable allocates a lot of contribution when describing purchasing decisions worth 64.30% while the remaining 35.70% is influenced by other indications outside of this study. The conclusion of the study is that price has a significant effect on the purchasing decision of students of the Faculty of Medicine UNPRI Medan where the sig < 0.05, brand image has a significant impact on the purchasing decision of students of the Faculty of Medicine UNPRI Medan where the sig < 0.05; Service quality has a significant impact on the decision to purchase a student at the Faculty of Medicine UNPRI Medan where the sig value is more than <0.05 and simultaneously price, brand image and service quality significantly affect the decision to purchase a student at the Faculty of Medicine UNPRI Medan where the sig value is <0.05.